2018
DOI: 10.1021/acs.inorgchem.8b02279
|View full text |Cite
|
Sign up to set email alerts
|

Not Just Par for the Course: 73 Quaternary Germanides RE4M2XGe4 (RE = La–Nd, Sm, Gd–Tm, Lu; M = Mn–Ni; X = Ag, Cd) and the Search for Intermetallics with Low Thermal Conductivity

Abstract: A total of 73 new quaternary rare-earth germanides RE 4 M 2 XGe4 (RE = rare-earth metal; M = Mn–Ni; X = Ag, Cd) were prepared through reactions of the elements. The solid solution Nd4Mn2Cd­(Ge1–y Si y )4 was also prepared under the same conditions and found to be complete over the entire range. All of these compounds adopt the monoclinic Ho4Ni2InGe4-type structure (space group C2/m, a = 14.2–16.7 Å, b = 4.0–4.6 Å, c = 6.8–7.5 Å, β = 106–109°), as revealed by powder X-ray diffraction analysis and single-crystal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…Other more successful experimental verification included the Heusler TiRu 2 Ga, whose preliminary results indicated that it had low thermal conductivity, and transition‐metal germanides Mn(Ru 0.4 Ge 0.6 ), whose thermal conductivity could be as low as 2 W m −1 K −1 . In addition, two quaternary rare‐earth germanides RE‐M‐M′‐Ge, i.e., Nd 4 Mn 2 InGe 4 and Nd 4 Mn 2 AgCe 4 , have also been synthesized and confirmed to have low thermal conductivities, in agreement with the engine prediction.…”
Section: Applicationmentioning
confidence: 83%
“…Other more successful experimental verification included the Heusler TiRu 2 Ga, whose preliminary results indicated that it had low thermal conductivity, and transition‐metal germanides Mn(Ru 0.4 Ge 0.6 ), whose thermal conductivity could be as low as 2 W m −1 K −1 . In addition, two quaternary rare‐earth germanides RE‐M‐M′‐Ge, i.e., Nd 4 Mn 2 InGe 4 and Nd 4 Mn 2 AgCe 4 , have also been synthesized and confirmed to have low thermal conductivities, in agreement with the engine prediction.…”
Section: Applicationmentioning
confidence: 83%
“…Machine learning and data mining have been successfully applied to materials problems across various domains. For example, they have been used to successfully identify new shape memory alloys, ferroelectric materials, and novel thermoelectrics, to make property predictions for heat capacity, , the band gap of crystalline solids, and elastic moduli, to optimize solar cells, to predict new phosphor materials, and to classify crystal structures of inorganic compounds. These methods generate predictions for unknown examples based on statistical relationships and patterns discovered using reliable data, informative descriptions of those data, and machine learning algorithms. In this work, we use a machine learning approach to build predictive models for interatomic distances.…”
Section: Resultsmentioning
confidence: 95%
“…Hirofumi Hazama,* Daisuke Murai, Naoyuki Nagasako, Masaki Hasegawa, and Nobuhiro Ogihara DOI: 10.1002/admt.202000254 understanding, can be constructed using machine learning techniques. While some of these machine learning techniques have been adopted, [1][2][3][4][5][6] most MI investigations are still conducted on the basis of computer simulations, as the simulations can intentionally change parameters without experimental errors. However, as it is difficult to obtain realistic data for complicated materials or systems from simulations, this should be supplemented with data collected from experiments.…”
Section: Optimization Of Materials Composition Of Li-intercalated Metamentioning
confidence: 99%